2022
DOI: 10.1186/s13765-022-00745-3
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of raspberry ketone from red raspberry and its intervention in the non-alcoholic fatty liver disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is characterized by diffused hepatocyte bullous fat in the liver, which is not caused by alcohol or drugs like amiodarone and tamoxifen. Presently, no drug is approved for NAFLD treatment. Therefore, it’s important to extract effective components from natural plants to alleviate NAFLD. In this study, we extracted and purified raspberry ketone, a natural phenolic compound from red raspberry (Rubus ideaus L.) by an ultrasonic-assisted ethanol extraction method. The struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…It is noteworthy that all the studies cited in Table IV , examining the effects of herbal plant extracts on IR, found significant decreases in glucose and insulin levels, as well as IR with the oral administration of these herbal extracts, namely, Abroma augusta (28,81). Aralia elata (84)(85)(86), Crocus sativus (97)(98)(99), Cyclosorus terminans (100-102), Glossogyne tenuifolia (80,103), Morus latifolia (107,108), Panax notoginseng (109), Pluchea indica (114), and Rubus ideaus (117,118), Trigonella foenum-graecum (119)(120)(121).…”
Section: Mechanism Of Actionsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is noteworthy that all the studies cited in Table IV , examining the effects of herbal plant extracts on IR, found significant decreases in glucose and insulin levels, as well as IR with the oral administration of these herbal extracts, namely, Abroma augusta (28,81). Aralia elata (84)(85)(86), Crocus sativus (97)(98)(99), Cyclosorus terminans (100-102), Glossogyne tenuifolia (80,103), Morus latifolia (107,108), Panax notoginseng (109), Pluchea indica (114), and Rubus ideaus (117,118), Trigonella foenum-graecum (119)(120)(121).…”
Section: Mechanism Of Actionsmentioning
confidence: 99%
“…Inflammation. The oral administration of extracts from various herbs, such as Antidesma bunius (83), Cassia obtusifolia (87), Crocus sativus (97), Cyclosorus terminans (101), Glossogyne tenuifolia (103), Hibiscus sabdariffa (105), Panax notoginseng (109) and Rubus ideaus (117), were found to lead to an improvement in the levels of inflammatory markers linked to liver damage. These herbal extracts have been found to reduce the levels of pro-inflammatory cytokines and inflammation.…”
Section: Mechanism Of Actionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, recent studies have revealed that raspberry ketones in cranberries can reduce non-alcoholic fatty liver disease by regulating glycolipid metabolism and reducing oxidative stress. Furthermore, raspberry leaf extract showed antioxidant, antibacterial, and anti-inflammatory activities ( Ma et al., 2022 ; Maslov et al., 2022 ). The high nutritional and medicinal value of raspberries opens possibilities for further development of therapeutics against lifestyle diseases gaining popularity worldwide, giving it the reputation of being the “fruit of life”.…”
Section: Introductionmentioning
confidence: 99%